Cross-Sectional Study of Efficacy, Effectiveness, and Safety of Combination Creams (Tretinoin 0.05%, Clindamycin 3%, and Dexamethasone 0.05%) Anti-Acne – An Online Study - Tan, Sukmawati Tansil; Yohanes Firmansyah; Hendsun Hendsun; Alicia Sarijuwita; William Gilbert Satyanegara; Joshua Kurniawan; Dean Ascha Wijaya (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Acne vulgaris is a common skin condition that causes blackheads, whiteheads, and pimples. It is caused by a number of things, like too much oil, clogged pores, and inflammation. Topical combination creams are an alternative treatment for acne. They can help reduce inflammation, kill bacteria that cause acne, and stop the skin from making too much oil. Topical combination creams like retinoids, antibiotics, and steroids are all mixed together in a single cream or gel. This study talks about the effectiveness and side effects of using combination creams (tretinoin 0.05%, clindamycin 3%, and dexamethasone 0.05%) to treat acne in the short and long term (local and systemic). Methods: This study is a survey that was done at the Sukma clinic with data from 2022 patients who were diagnosed with acne vulgaris. The survey was done on Google Forms, which is a website. In this study, different factors were looked at, such as demographics, efficacy (like reducing acne severity, making the skin brighter, getting rid of blackheads on the face, getting rid of acne scars, improving skin texture, hiding scars, minimizing facial pores, getting rid of wrinkles and dark spots), local adverse events (like burning, itching, stinging, eruptive papules, hypopigmentation, hyperpigmentation, erythema, scaling, and other), and systemic adverse events. Results: The results of this study show that a combination of tretinoin 0.05%, clindamycin 3%, and dexamethasone 0.05% is very effective and has minimal side effects. Local symptoms only show up during the first week of taking the drug (the "sensitization phase"), and then they tend to get less common over time. The only exceptions are hyperpigmentation and hypopigmentation, which show up later because they are caused by healing acne lesions. Conclusion: There was no direct link between the use of anti-acne combination cream drugs and the number of systemic side effects. This is because the patient had often had this happen before (constipation, GERD, and others).